Physical unclonable function: architectures, applications and challenges for dependable security. Issue 4 (19th March 2020) - Ning, Huansheng; Farha, Fadi; Ullah, Ata; Mao, Lingfeng
Abstract : Physical unclonable function (PUF) is hardware‐specific security primitive for providing cryptographic functionalities that are applicable for secure communication among the embedded devices. The physical structure of PUF is considered to be easy to manufacture but hard or impossible to replicate due to variations in its manufacturing process. However, a large community of analytics believes hardware‐based PUF has paved the way for its realisation in providing dependable security. In this study, the authors have thoroughly explored the architecture, applications, requirements, and challenges of PUF that provide security solutions. For presenting the literature, they have designed a taxonomy where PUFs are divided under two main categories, including non‐silicon and silicon‐based PUF. Currently, there is no comprehensive survey that highlights the comparison and usability of memory‐based and analogue/mixed‐signal based PUF that are considered to be suitable as compared to counterparts. In a similar vein, they have presented the network‐specific application scenarios in wireless sensor network, wireless body area network and Internet of Things and then identified the strong, weak and controlled PUF in a categorical manner. Moreover, they have presented a number of prospective limitations that are identified in PUF structures and then identified the open research challenges to meet the desired security levels.